2018
DOI: 10.1186/s12935-018-0539-6
|View full text |Cite
|
Sign up to set email alerts
|

Epistructured catechins, EGCG and EC facilitate apoptosis induction through targeting de novo lipogenesis pathway in HepG2 cells

Abstract: BackgroundAbnormally high expression of the mammalian de novo lipogenesis (DNL) pathway in various cancer cells promotes cell over-proliferation and resistance to apoptosis. Inhibition of key enzymes in the DNL pathway, namely, ATP citrate lyase, acetyl-CoA carboxylase, and fatty acid synthase (FASN) can increase apoptosis without cytotoxicity to non-cancerous cells, leading to the search for and presentation of novel selective and powerful targets for cancer therapy. Previous studies reported that epistructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 62 publications
3
32
0
Order By: Relevance
“…Conversely, the water extract of B. speciosa was able to reduce cell viability in the concentration range (300-500 µg/mL) throughout the 72 hour treatment (Figure 1), thus indicating significant anti-proliferative effects that are consistent with more than one speculation. On one side, the concentration-dependent anti-proliferative effects that were exerted by the water extract could be related to epicatechins [51]. This was, at least in part, confirmed by the mild anti-proliferative effect that was exerted by the sole epicatechin (100 µg/mL) (CTR: 100; Epicatechin: 87.88 ± 4.35).…”
Section: Resultsmentioning
confidence: 75%
“…Conversely, the water extract of B. speciosa was able to reduce cell viability in the concentration range (300-500 µg/mL) throughout the 72 hour treatment (Figure 1), thus indicating significant anti-proliferative effects that are consistent with more than one speculation. On one side, the concentration-dependent anti-proliferative effects that were exerted by the water extract could be related to epicatechins [51]. This was, at least in part, confirmed by the mild anti-proliferative effect that was exerted by the sole epicatechin (100 µg/mL) (CTR: 100; Epicatechin: 87.88 ± 4.35).…”
Section: Resultsmentioning
confidence: 75%
“…In addition, osteoclastic cell death was induced by ROS produced by EGCG (12.5–100 μm) 29. It had also been demonstrated that EGCG (0.5 mM) increased ROS generation, the mPTP opening as well as apoptosis level in HepG2 cells 30. We hold the opinion that the various and opposing effects of EGCG may depend on the different dosage, cellular condition and cell types.…”
Section: Discussionmentioning
confidence: 73%
“…Different studies report that catechins [41, 42], anthraquinones [39], and piceatannol [43, 44] induce apoptosis in tumor cells. Corroborating this is the analysis of the mechanism whereby ESVR-promoted B16F10-Nex2 cell death showed an increased number of apoptotic nuclei, which are characterized by chromatin condensation and DNA fragmentation, characteristic stages of death by apoptosis [45].…”
Section: Discussionmentioning
confidence: 99%